Low temperature solution-phase growth of ZnSe and ZnSe/CdSe core/shell nanowires - Petchsang, Nattasamon (2011)
High quality ZnSe nanowires (NWs) and complementary ZnSe/CdSe core/shell species have been synthesized using a recently developed solution-liquid-solid (SLS) growth technique. In particular, bismuth salts as opposed to pre-synthesized Bi or Au/Bi nanoparticles have been used to grow NWs at low temperatures in solution. Resulting wires are characterized using transmission electron microscopy and possess mean ensemble diameters between 15 and 28 nm with accompanying lengths ranging from 4-10 μm. Subsequent solution-based overcoating chemistry results in ZnSe wires covered with CdSe nanocrystals. By varying the shell's growth time, different thicknesses can be obtained and range from 8 to 21 nm. More interestingly, the mean constituent CdSe nanocrystal diameter can be varied and results in size-dependent shell emission spectra.